Asymmetric Total Synthesis of Four Stereoisomers of the Sex Pheromone of the Western Corn Rootworm - Sun, Zhi-Feng (Molecules, 2018)
A convergent synthesis of four stereoisomers of the sex pheromone of the western corn rootworm (8-methyldecan-2-yl propionate, 1) from commercially available chiral starting materials is reported. The key step was Julia–Kocienski olefination between chiral BT-sulfone and chiral aldehyde. This synthetic route provided the four stereoisomers of 1 in 24–29% total yield via a six-step sequence. The simple scale-up strategy provides a new way to achieve the asymmetric synthesis of the sex pheromone.